Update on Pathogenesis of Glomerular Hyperfiltration in Early Diabetic Kidney Disease - Yang, Yang; Xu, Gaosi (Frontiers in Endocrinology, 2022)
In the existing stages of diabetic kidney disease (DKD), the first stage of DKD is called the preclinical stage, characterized by glomerular hyperfiltration, abnormally elevated glomerular filtration rate (GFR). Glomerular hyperfiltration is an independent risk factor for accelerated deterioration of renal function and progression of nephropathy, which is associated with a high risk for metabolic and cardiovascular disease. It is imperative to understand hyperfiltration and identify potential treatments to delay DKD progression. This paper summarizes current mechanisms of hyperfiltration in early DKD. We pay close attention to the effect of glucose reabsorption mediated by sodium-glucose cotransporters (SGLTs) and renal growth on hyperfiltration in DKD patients. As well as the mechanisms of nitric oxide (NO) and adenosine actions on renal afferent arterioles via tubuloglomerular feedback (TGF). Furthermore, we also focus on the contribution of atrial natriuretic peptide (ANP), cyclooxygenase (COX), renin-angiotensin-aldosterone system (RAAS), endothelin as hormones and vasoactive mediators on hyperfiltration.